Exploratory study on First-generation College Students’ experiences and their assessment of Affirmative Action Programs (Praxis Educativa, 2022)
This qualitative study analyzed the first-generation college students’ experiences in higher education and their assessment of two programs of access to and persistence, which have been implemented as a public policy in Chile for more than a decade. Using a phenomenological approach, in-depth semi-structured interviews were conducted with 12 participants, six who accessed through those programs and six who enrolled through the regular national admission system (PSU). The main results show that first-generation students, regardless of the way of access to higher education, have similar experiences in terms of university adjustment. In addition, those programs mainly FGS’s meet access equity. Finally, this study also refers to some unique experiences regarding being FGS, which have not yet been addressed in previous studies.
Keywords: higher education; university student; educational policy; access to education; compensatory education